Penerapan Arsip Elektronik dan Pengaruhnya Terhadap Peningkatan Kinerja Pegawai di PT. Perusahaan Listrik Negara (Persero) Unit Induk Wilayah Maluku dan Maluku Utara - Aihunan, Sakina Safarina; Ohoiwutun, Stanislaus Kostka; Ufi, Josep Antonius; Patty, Julia Theresia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the management of electronic archives across various institutions, focusing on effectiveness, efficiency, and its impact on employee performance. The study examines different strategies for optimizing digital archiving systems, including the implementation of correspondence management applications and relevant policies adopted by both the government and the private sector. Using a quantitative approach, this research is analyzed through statistical methods. The findings indicate that the implementation of digital archiving systems can improve work efficiency, reduce the risk of document loss, and accelerate access to information. However, challenges such as limited technological infrastructure, lack of employee training, and data security issues remain major obstacles to the successful implementation of these systems. Therefore, more comprehensive policies and ongoing training are needed to ensure the sustainability of effective and secure electronic archive management.